EFFICACY OF TAP BLOCK AND PLACEBO FOR PAIN IN PATIENTS UNDERGOING CSECTION SURGERY - Usman Khalid (Army Medical College Rawalpindi, 2021)
Objective: To compare efficacy of transversus abdominis plane block and placebo for pain in patients undergoing C-section surgery.